P Peningkatan Pemahaman Siswa SMK Pandanaran Tentang Kenakalan Remaja Di Era Digital: Peningkatan Pemahaman Siswa SMK Pandanaran Tentang Kenakalan Remaja Di Era Digital - Helen Intania Surayda; Tri Mulyani; Khaidar Elifika El Ula; Rico Setyo Nugroho (Forum Komunikasi Dosen, 2025)
Adolescence is a critical period in preparation for adulthood. The WHO states that those aged 10-24 are vulnerable to the effects of smartphones, and this age group is the largest internet user. This is consistent with the APJII (Indonesian Internet Service Providers Association) report on internet users in 2022, which found that the highest number of internet users were teenagers aged 13-18, with a percentage reaching 99.16%. Teenagers in the digital era are increasingly accessing online games, and the worst case scenario is getting caught up in online gambling. UNICEF states that teenagers are highly vulnerable to online gambling, even two to four times more than adults. Juvenile delinquency in the digital era, particularly related to online gambling, is a worrying phenomenon that can lead to addiction, mental health disorders, financial ruin, and other deviant behavior. Based on this, the problem in this Community Service (PKM) activity can be formulated as a lack of understanding among Pandanaran Vocational School students about juvenile delinquency in the digital era and how to overcome it. This PKM activity was conducted using lectures, discussions, and question-and-answer methods. In this PKM activity, SMK Pandanaran students obtained information developments and increased their understanding of juvenile delinquency in the digital era, as shown by an average increase in general understanding of 19 participants of 38.95%.